Angiomatous pleomorphic xanthoastrocytoma: a case report and literature review - Jiang, Yue-Feng (Diagn Pathol, 2016)
BACKGROUND: Pleomorphic xanthoastrocytoma is rare, accounting for <1 % of all central nervous system (CNS) neoplasms. Angiomatous pleomorphic xanthoastrocytoma is an extremely rare variant of pleomorphic xanthoastrocytoma, with only six cases reported thus far. CASE PRESENTATION: A 24-year-old Chinese female patient who presented with seizure and loss of consciousness for 15 min underwent computed tomography and magnetic resonance imaging, which revealed a mass in the left parietal lobe. Histologically, the tumor was characterized by pleomorphic tumor cells and prominent vascularity. The angiomatous region varied, ranging from a sinusoidal pattern to a venous malformation. Focal fibrinoid necrosis, hyalinization, and a moderate infiltration by lymphocytes and plasma cells were visible in the vessel wall. The tumor cells were in close proximity with adjacent small vessels. Capillaries adjacent to or extending between tumor cells were focally observed. Most tumor cells were positive for glial fibrillary acidic protein and oligodendrocyte lineage transcription factor 2. The Ki-67 index was low. Based on the patient’s history, clinical data, and pathological findings, she was diagnosed with angiomatous pleomorphic xanthoastrocytoma (WHO grade II). CONCLUSIONS: This case serves as a reminder to pathologists of the need to be aware of this rare variant of pleomorphic xanthoastrocytoma to avoid a misdiagnosis of this indolent CNS tumor and therefore inappropriate treatment.